Secretion of Atrial Natriuretic Peptide (ANP), Heart Reconditioning and Remolding in Elite Endurance Trained Athletes - Hafeezullah Wazir Ali, Mohammad Aslam, Sohail Aziz, Muhammad Mazhar Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim / Objective: The aim of this study was to evaluate the effect of maximal exercise on the level of cardiac remolding and Atrial Natriuretic Peptide (ANP) in elite athletes as compared to sedentary healthy subjects and correlation of ANP with the adaptation of athlete’s heart and cardiac remodeling (if any) Place and Duration of Study: The present study was carried out at the Department of Physiology, Army Medical College, with collaboration of Armed Forces Institute of Cardiology (AFIC) Rawalpindi from June 2003 to May 2004. Methodology: A total number of 44 subjects were included in this study. These comprised of 22 elite endurance athletes and 22 healthy sedentary volunteers as controls. All subjects were examined clinically to rule out the cardiovascular and pulmonary diseases on the basis of medical history, physical examination, and echocardiography. All the selected subjects were examined on a Toshiba Power Vision 6000 echocardiograph for assessing and measuring their LV end-diastolic internal diameter (LVIDd), Diastolic interventricular septal thickness (IVSTd), diastolic posterior wall thickness (PWTd). The left ventricular mass was (LVM) was calculated by using the Devereux formula. They were subject to go for ergometer cycle exercise before breakfast. The Blood samples were drawn before and after exercise to assess the level of ANP in their samples. Results: It was found that LVIDd, IVSTd, PWTd, LVM were higher in athletes as compared to their age, sex and BMI matched controls. The ANP levels in athlete’s plasma were also high in post and pre exercise sample as compared to controls. Conclusion: Systolic blood pressure, Diastolic Blood Pressure and heart rate are lower in endurance elite athletes than matched sedentary controls. The maximal Exercise increases the level of Atrial Natriuretic Peptide (ANP) in elite athletes significantly as compared to sedentary healthy controls. There was a Positive correlations between ANP and LVIDd, IVSTd, PWTd, and LVM while there was negative correlation between ANP and heart rate, ANP and Blood pressure. However, none of correlation was found to be statistically significant.